Les récréations scientifiques : diffusion et succès de l’œuvre de vulgarisation de Gaston Tissandier en Espagne à la fin du XIXe siècle - Sablonnière Catherine (Amnis)
During the last quarter of the 19th Century, Gaston Tissandier produced an original collection of popular science works emphasizing learning through play. His writings and the illustrations contained in his books and articles were innovative. Most of his works were translated into many languages, including Spanish. Publishing strategies can partly, but not solely, explain why his works spread outside France. In Spain, many extracts from the review “Nature” and “Scientific Recreations” were published in the illustrated magazines and in republican or “regerationist” periodicals. G. Tissandier is rarely quoted as author of these extracts. However their existence reveals an appetite for these new scientific teachings, which were also supported by the krausist reformers who had read F. Fröbel and M. Pape-Carpantier. At a time of insufficiency of the scientific textbook market, the works of Tissandier will serve as a model and inspire original and progressive school and popular works influenced by the secular and scientifically rigorous approach of G. Tissandier.